The conserved Cys76 plays a crucial role for the conformation of reduced glutathione peroxidase-type tryparedoxin peroxidase - Muhle-Goll, Claudia; Füller, Florian; Ulrich, Anne S.; Krauth-Siegel, Renate (FEBS letters, 2010)
The crystal structure of reduced tryparedoxin peroxidase shows Cys47 close to Gln82 and Trp137 and helix formation of residues 87 to 97 whereas the NMR structure of the reduced C76S mutant adopts a different conformation similar to the oxidized protein. Circular dichroism (CD), fluorescence and NMR spectroscopy reveal that the fully active C76S mutant differs from the wildtype (WT) enzyme mainly in its reduced form both in secondary structure content and Trp137 environment. This implies that Cys76 plays a critical role for the reduced enzyme assuming different conformational states and that the catalytic triad may only be necessary as short-lived intermediate during catalysis.
Gesehen am 12.05.2023